THE DEMOTIVATION PHENOMENON OF LEARNING ARABIC IN THE NEW NORMAL ERA AT MADRASAH ALIYAH DARUDDA'WAH WAL-IRSYAD KIJANG ISLAND - Dina Novita; Muhammad Sobri; Sulhi M. Daud (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The purpose of this study is to find out the process of learning Arabic in the new normal era, the demotivating phenomenon of learning Arabic, the teacher's obstacles in overcoming the demotivation of learning Arabic, and the solution to the demotivating phenomenon of learning Arabic in the new normal era. This study uses a qualitative method with a qualitative descriptive approach. Well, interviews, observations, and documentation a comprehensive data collection techniques. The results showed that there was demotivation in learning Arabic in class X IPS MA DDI Kijang Island, evidenced by internal and external factors which showed that: 1) students were less active and enthusiastic in learning Arabic, 2) Students found it difficult to learn Arabic. Arabic, 3) Changes in unscheduled learning conditions, 4) The methods used by teachers are less varied, 5) Limited duration of learning, 6) Less conducive learning environment. The teacher's efforts and solutions to overcome demotivation and increase motivation to learn Arabic are as follows: 1) Become a cool teacher, 2) Encourage students to keep practicing, 3) Score points and praise. The previous research was conducted before the pandemic face-to-face, while this research was conducted online during the pandemic.